GELANG BEL RUMAH UNTUK PENYANDANG TUNARUNGU MENGGUNAKAN MODUL RF 433MHZ - Ira Puspita Sari; Luluk Elvitaria; Syaid Alarbi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
This research addresses the design of hardware to assist individuals with hearing loss. The system consists of a transmitter mounted on a door and a receiver worn on the wrist. The user can connect the device by pressing a button on the wristband, and the transmitter sends a command signal to the receiver. The receiver activates the vibrator motor, which produces vibrations for 2 seconds. The communication range is within a radius of several hundred meters under optimal conditions, using common and less congested radio frequencies. The RF module used in the system operates at a frequency of 433MHz and uses Amplitude Shift Keying (ASK) modulation. The system uses a flashing LED to indicate the command signal. The LED blinks for a specific duration, and the blinking pattern can be controlled. The system also includes a data reception function, where received data is checked for specific messages and processed accordingly.